Efeito da adição de hexametafosfato de sódio em um gel com reduzida concentração de fluoreto na remineralização do esmalte dentário: estudo in vitro - Gonçalves, Francyenne Maira Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Proposition: To evaluate in vitro, the ability of a neutral pH topical gel with reduced fluoride concentration and supplemented or not with sodium hexametaphosphate (HMP) on the remineralization of dental enamel, using a pH-cycling model. Materials and methods: Bovine enamel blocks (n = 120) were selected through surface hardness (SH) and subjected to demineralization for 16 hours. Thus, SH after demineralization (SH1) was determined, and divided into five treatment groups (n = 24): 1) Gel without F/HMP (Placebo); 2) Gel 4.500 μg F/g (4500), 3) Gel 4.500 μg F/g associated 9% HMP (4500, 9%HMP); 4) Gel 9.000 μg F/g (9000); and 5) Gel 12.300 μg F/g (Acid gel). The blocks were subjected to six pH cycles (demineralizing/remineralizing solutions) at 37°C. Subsequently, after remineralization SH (SH2), percentage of SH recovery (%SHR), and integrated loss of subsurface hardness (ΔKHN) were assessed, and the concentrations of calcium fluoride (CaF2) and fluoride (FA) formed and retained were determined. The results were subjected to ANOVA followed by Student-Newman-Keuls test (p < 0.001). Results: The 4500 9%HMP group showed higher SH2 and %SHR values when compared to the other groups (p < 0.001). The 4500 9%HMP and Acid gel groups showed similar results and the lowest mineral loss (ΔKHN) (p > 0.001). The Acid gel group presented the highest CaF2 and FA formed and retained concentration in enamel (p < 0.001). Conclusion: The 9% HMP addition to a low-fluoride gel concentration was able to promote the remineralization of artificial caries lesions in this in vitro study

Proposição: Avaliar in vitro a capacidade de um gel tópico de pH neutro com reduzida concentração de fluoreto e suplementado ou não com hexametafosfato de sódio (HMP) na remineralização do esmalte dental, usando um modelo de ciclagem de pH. Materiais e Métodos: Blocos de esmalte bovino (n = 120) foram selecionados através da dureza da superfície (SH) e submetidos a desmineralização durante 16 horas. A seguir, SH pós-desmineralização (SH1) foi determinada e dividido em cinco grupos de tratamento (n = 24): 1) Gel sem F/HMP (Placebo); 2) Gel 4,500 μg F/g (4500), 3) Gel 4,500 μg F/g associado a 9% HMP (4500 9%HMP); 4) Gel 9,000 μg F/g (9000) e 5) Gel 12,300 μg F/g (Gel ácido). Os blocos foram submetidos a seis ciclagens de pH (soluções de desmineralização/remineralização) a 37 °C. Posteriormente, foi avaliada a SH pós-remineralização (SH2), porcentagem de recuperação de SH (%SHR), perda integrada de dureza de subsuperfície (ΔKHN), e as concentrações de fluoreto de cálcio (CaF2) e fluoreto (FA) formado e retido no esmalte foram determinadas. Os resultados foram submetidos a ANOVA seguido pelo teste Student-Newman-Keuls (p < 0,001). Resultados: O grupo 4500 9%HMP apresentou os maiores valores de SH2 e %SHR quando comparado aos demais grupos (p < 0,001). Os grupos 4500 9%HMP e Gel ácido apresentaram resultados similares e a menor perda mineral (ΔKHN) (p > 0,001). O grupo Gel ácido apresentou alta concentração de CaF2 e FA formado e retido no esmalte (p < 0.001). Conclusão: A adição de 9%HMP a um gel de baixa concentração de fluoreto foi capaz de promover a remineralização de lesões artificiais de cárie neste estudo in vitro
Keywords: Esmalte dentário; Fluoretos; Fosfatos; Remineralização dentária; Dental enamel